Iron and Steel Unionism in Canada and Australia, 1900-1914: The Impact of the State, Ethnicity, Management, and Locality - Patmore, Greg (Labour / Le Travail, 2006)
Compared to Canada, Australian trade union membership grew dramatically in the period from 1900 to 1914. Through a comparative analysis of two iron and steel plants in Canada and Australia, this article broadens the debate about union growth in this particular period as well as generally. One plant was located at Lithgow, New South Wales, and the other at Sydney, Nova Scotia. While workers at both plants unionized in September-October 1902, the union at the Sydney plant collapsed following a major strike in 1904. Iron and steel unionism did not revive at the Sydney plant until during World War I. With the exception of a brief period, iron and steel unionism continued at the Lithgow plant for the period under examination. This article attempts to explain why iron and steel unionism persisted at Lithgow rather than Sydney and focuses on the factors of the state, the ethnic diversity of the workforce, management, and community or locality.
Keywords: CULTURAL fusion; CULTURAL pluralism; ETHNIC groups; GROUP identity; LABOR supply; Labor Unions; Labor disputes; MULTICULTURALISM; Steel industry